Primary Hepatic Tuberculosis: An Unexpected Diagnosis - Hasan, SM Ali; Hassan, Nazmoul; Hossain, Delwar; Islam, AKM Shafiqul; Abedin, Forhad; Jamal, Shah; Hoque, Izazul (Journal of Comilla Medical College Teachers’ Association, 2023)
Background: Primary hepatic tuberculosis (PHT) is a rare form of extrapulmonary tuberculosis that affects the liver and is difficult to diagnose. The present case report describes a patient who was diagnosed with PHT and was successfully treated with a combination of anti-tuberculosis drugs. A 55-year-old diabetic male presented with a history of abdominal pain, fever and weight loss. An abdominal ultrasound and computed tomography (CT) scan revealed multiple hepatic lesions, and fine needle aspiration cytology confirmed the diagnosis of PHT. The patient was treated with a standard regimen of isoniazid, rifampin, pyrazinamide, and ethambutol for two months, followed by isoniazid and rifampin for another four months. The patient showed improvement in symptoms and the disappearance of hepatic lesions, as seen on follow-up ultrasound scans. This case highlights the importance of considering PHT in the differential diagnosis of patients with hepatic lesions, particularly in regions with a high burden of tuberculosis. Early diagnosis and prompt treatment can lead to a good outcome in PHT. J Com Med Col Teachers Asso Jan 2023; 27(1): 38-41